Higher education and health at midlife: Evaluating the role of college quality - Jia Wang; Jordan Conwell (Elsevier, 2022)
Using the longitudinal data from the National Longitudinal Survey of Youth-1979 linked with external data on college characteristics (N = 7056), this study illustrates an independent stratifying role of college quality in shaping health. College quality has significant and positive influences on physical health, and this positive association tends to strengthen across 40 and 50. By contrast, attending higher-quality colleges is not associated with mental health at either age 40 or age 50. Decompositions were conducted to assess the extent to which early life and demographic characteristics, employment and economic conditions, health behaviors, and family relationships account for observed patterns. Our study highlights the necessity for future research on education and health to incorporate characteristics of schools attended; reveals variation in the college quality-health nexus by specific health outcomes; and provides new insights into understanding health inequalities across the life course.